Analisis Frasa dalam Teks Esai pada Buku Bahasa Indonesia Kelas XII Kurikulum Merdeka (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
The main discussion in this research article is the analysis of phrases that have a function in observing the use of the types of phrases contained in the essay text entitled "Dusta yang Jujur" and "Godaan". There is also a purpose in conducting this research, namely to inform, classify, and describe the types of phrases in the essays listed in Giyato's Dusta yang Jujur and Goenawan Mohamad's Godaan. The type of research in this article is a type of descriptive qualitative research. Data collection methods and techniques applied in this study are the observing methods and the note-taking technique. Data collection refers to the essay text in the Class XII book of the Merdeka Curriculum. The objects of research in this article are the essay entitled Dusta yang Jujur by Giyato which has 3 pages and the text of the essay entitled Godaan by Goenawan Mohamad in the Indonesian language book Class XII of the Merdeka Curriculum. With this research on phrases, it is hoped that readers will be able to find out the types of phrases contained in the essay text entitled Dusta yang Jujur by Giyato which has 3 pages, and the text of the essay entitled Godaan by Goenawan Mohamad in the Indonesian language book class XII of the Merdeka Curriculum.